2021
DOI: 10.3390/antiox10121951
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 Applied after Exposure Attenuates Damaging Effects of X-ray Radiation in 3T3 Mouse Fibroblasts

Abstract: Although many different classes of antioxidants have been evaluated as radioprotectors, none of them are in widespread clinical use because of their low efficiency. The goal of our study was to evaluate the potential of the antioxidant protein peroxiredoxin 6 (Prdx6) to increase the radioresistance of 3T3 fibroblasts when Prdx6 was applied after exposure to 6 Gy X-ray. In the present study, we analyzed the mRNA expression profiles of genes associated with proliferation, apoptosis, cellular stress, senescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We suggest that these results are attributable to the ability of Prdx6 to stimulate insulin production in pancreatic β-cells [99], which should clearly affect the insulin resistance characteristic of type 2 diabetes. In addition, using 3T3 fibroblasts, Prdx6 reduced cell senescence caused by a sublethal dose of X-ray radiation [105]. This finding indicates that Prdx6 may be included in the list of senolytics.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 79%
“…We suggest that these results are attributable to the ability of Prdx6 to stimulate insulin production in pancreatic β-cells [99], which should clearly affect the insulin resistance characteristic of type 2 diabetes. In addition, using 3T3 fibroblasts, Prdx6 reduced cell senescence caused by a sublethal dose of X-ray radiation [105]. This finding indicates that Prdx6 may be included in the list of senolytics.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 79%
“…[ 26 ]. This is apparently the reason why exogenous Prdx6 effectively eliminates intracellular peroxides [ 26 ], as well as lowers the level of the redox-sensitive transcription factor p53, which promotes a suppression of senescence and apoptosis of irradiated cells [ 37 ]. Apart from this, we have recently shown that overexpression of exogenous Prdx6 in the cells also causes p53 suppression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps it is due to the phospholipase activity that exogenous Prdx6 not only directly affects the level of intracellular ROS, but also takes part in the redox relay regulation of the most important transcription factors [ 3 , 26 , 37 ], thus influencing the fate of the cell ( Figure 8 ). Additionally, exogenous Prdx6 activates NF-κB expression through TLR4 stimulation [ 26 ] and inhibits p53 activity [ 37 ], which promotes cell survival under conditions of oxidative stress caused by ionizing radiation. It has been recently shown that Prdx6 is capable of forming cation-selective ion channels in artificial membranes [ 53 ], which are selective to Ca 2+ [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation (IR) is the energy released by atoms in the form of electromagnetic waves (e.g., X or gamma rays) or particle radiation (alpha, beta, electrons, protons, neutrons, mesons, prions, and heavy ions) with sufficient energy to ionize atoms or molecules [ 1 ]. IR induces DNA breaks leading to direct molecular damages or even cell death, whereas in the case of cell survival, it can lead to carcinogenesis or other abnormalities [ 2 , 3 ]. The highly reactive free radicals formed by the radiolysis of water (superoxide anion (O 2 •− ), hydroxyl radical (•OH), hydrated electron (e − (aq) ), and hydrogen peroxide (H 2 O 2 )) and the subsequent oxidative stress are the main cause of most of the molecular (DNA, lipids, proteins, etc.)…”
mentioning
confidence: 99%
“…The first ones reduce or prevent the damage induced by IR (generally acting as chelators of free radicals, antioxidants, …), but to be effective, they must be administered before or at the same time as exposure [ 2 ]. In contrast, radiomitigators help to recover or attenuate radio-induced damages even when they are administered after radiation exposition [ 3 , 7 ], which represents an important strategic advantage. Mechanisms involved in the radiomitigating activity include the restoration of the cellular antioxidant defence mechanisms, the prevention of excessive inflammatory responses, and/or the repair of damaged tissues [ 5 ].…”
mentioning
confidence: 99%